posted by lily on .
What is 7(y+3)+2y simplified? and if possible, can you break down how you got it?
Simplifying equations confuses me easily.
7y + 21 + 2y
9y + 21
multiply 7 with y and 3
collect like terms
Tasuba -- I think you've misread the problem. I don't see any minus signs in the original problem.
The first thing you should do is try to remove the brackets. You can do this by using distributivity. In symbols, this means the following:
a*(b + c) = a*b + a*c
As you can see, the first term of the equation is 7*(y+3)
So, using distributivity, we find that
7*(y+3) = 7*y + 7*3 = 7y + 21
So, the equation can be simplified in the following manner:
7(y+3)+2y = 7y + 21 + 2y
Now, we have to terms with y. if we put them together, we get:
7y + 2y + 21
If we use the formula of distributivity in reverse, we find that:
7y + 2y = (7+2)*y = 9y
So, the equation can be further simplified in the following manner:
7y+2y+21 = 9y + 21